Bridging the gap: Understanding, anticipating, and responding to the needs of student veterans in a bachelor of science in nursing program. - Stowers, Larry Michael (Bridging the Gap: Understanding, Anticipating & Responding to the Needs of Student Veterans in a Bachelor of Science in Nursing Program, 2014)
The passage of the Americans with Disabilities Act Amendment Act (ADAAA) of 2008 and the Post-9/11 Veterans Assistance Act of 2008 have afforded veterans the opportunity to pursue post-secondary education. Since October 2001, over 2 million American men and women in uniform have deployed in support of Operation Enduring Freedom (OEF) and Operation Iraqi Freedom (OIF). While thousands of returning combat veterans take advantage of recent legislation that helps pay for their education, they face new challenges in the classroom. This nation's veterans represent a group of diverse individuals who bring different experiences, thus different perspectives than traditional college-aged students. However, the additional burden of adjusting to the effects of combat, often after multiple tours in combat zones, may interrupt veterans' transition from the military back into civilian life and the classroom. The personal and cultural characteristics common to returning veterans need to be an essential element for postsecondary institutional faculty development. Focusing on student retention through prevention and early identification of service-related problems and, when appropriate, early referral to University and community resources is critical. Understanding student veterans means understanding military culture, battlefield skills, and deployment related stressors. It also means listening to students' stories and understanding the unique stressors faced by student veterans on campus. The purpose of this Doctor of Nursing Practice (DNP) capstone project was to develop a program to educate University of Southern Mississippi (USM) College of Nursing (CoN) faculty and staff about the issues and challenges of serving veteran students, especially those with diagnosed or undiagnosed Post-Traumatic Stress Disorder (PTSD) and service-related disabilities.